Dose from Naturally Occurring Radium Radioactivity in Abstracted Disi Fossil Groundwater* - Saed Dababneh (Jordan Journal of Physics, 2025)
The radium activity concentration data measured by Vengosh et al. [1] in water samples from the Disi aquifer are utilized to calculate the annual effective dose delivered to adult human consumers. Although the total activity in the Rum group in particular is significantly high compared to the very conservative World Health Organization WHO guidelines, the calculated average effective dose is slightly higher than the Jordanian standard and less than the corresponding value in the Australian guidelines. Blending models are suggested which reduce the dose and its associated risks. The results reveal the radiological quality of the indispensable Disi drinking-water to be satisfactory for consumption in a water-poor part of the World. Keywords: Radioactivity; Disi aquifer; Disi conveyance project; Groundwater; Dose; Risk assessment. PACS: 89.60.-k; 92.40.Kf; 92.40.kh; 92.40.kc; 67.63.-r; 67.80.F